2017
DOI: 10.5588/ijtld.16.0716
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-resistant tuberculosis: a cause for concern?

Abstract: SUMMARY The drug isoniazid (INH) is a key component of global tuberculosis (TB) control programmes. It is estimated, however, that 16.1% of TB disease cases in Former Soviet Union countries and 7.5% of cases outside of those settings have non-multidrug resistant (MDR) INH resistance. Resistance has been linked to poorer treatment outcomes, post-treatment relapse and death, at least for specific sites of disease. Multiple genetic loci are associated with phenotypic resistance, but the relationship between genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 82 publications
(84 reference statements)
1
64
0
5
Order By: Relevance
“…Conversely, one isolate was INH resistant but sensitive to rifampin. Thus, detection of RIF or INH resistance via analysis of either rpoB or katG genes alone may not accurately confirm MDR-TB, resulting in patients with non-MDR INH resistance at risk of being treated inadequately (35).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, one isolate was INH resistant but sensitive to rifampin. Thus, detection of RIF or INH resistance via analysis of either rpoB or katG genes alone may not accurately confirm MDR-TB, resulting in patients with non-MDR INH resistance at risk of being treated inadequately (35).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to INH is linked to all multidrug-resistant forms of TB (MDR, XDR, TDR). Several studies have shown that INH resistance is acquired first, followed by resistance to rifampin and the other anti-TB drugs (32-36), which highlights the significant impact of INH in the success of treatment in active and latent TB and warrants further efforts to understand the global burden of INH-resistant TB (37). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…23 Development of INH resistance precedes the development of MDR-TB. 24 Initial INH resistance increases incidence rates of treatment failure and relapse compared with pan-sensitive strains (incidence rate ratio 10.9 and 1.8, respectively). 25 Research priorities include the development of a strong evidence base for the optimal use of preventive therapy in high-risk populations, determining the protective efficacy of novel vaccines, developing sensitive and rapid diagnostic tests for DR-TB (directly from sputum samples), identifying biomarkers to predict future disease risk, identifying pragmatic methods to enhance case detection, testing new models of care to reduce time to effective treatment, developing treatment regimens that are short, safe and durable and improving infection control in all high-transmission settings.…”
Section: Discussionmentioning
confidence: 99%